Photoluminescence investigations of sulfur quantum dots synthesized by a bubbling-assisted strategy. Issue 14 (24th June 2021) - Liu, Shuo; Wang, Henggang; Feng, Anrui; Chang, Jianyu; Zhang, Chuanchuan; Shi, Yu-e; Zhai, Yongqing; Biju, Vasudevanpillai; Wang, Zhenguang
Abstract : The photoluminescence mechanisms of S-dots were revealed by the bubbling-assisted synthesis and spectroscopic study. The emission color of the S-dots depends on the size, and the emission efficiency is affected by the surface sulfur species. Abstract : Sulfur quantum dots (S-dots) emerge as promising luminescent materials owing to their remarkable optical properties. However, the mechanisms of their formation and photoluminescence remain concealed. We reveal these mechanisms by the bubbling-assisted synthesis and spectroscopic study of S-dots formed from sulfur ions produced by the alkaline oxidation of bulk sulfur under the passivation of PEG. The emission colour of the S-dots depends on the size, explained by the quantum confinement effect. The dots' luminescent quantum efficiency is strongly affected by the surface sulfur species, which is optimized by the proper surface oxidation. The simple synthesis, excellent luminescence properties, and metal-free nature attract S-dots to optoelectronic and electroluminescence applications.